SOME ASPECTS OF ORGANIZING COST ACCOUNTS IN FRUIT AND VEGETABLE FARMS (World Economics and Finance Bulletin, 2025)
The article examines some aspects of cost accounting in fruit and vegetable farms. The approaches and opinions of economists and experts regarding the concept of costs are studied, conclusions and proposals are developed